Demographic Study of Trachoma Patients and Their Response to Azithromycin - Abdul Baseer, Sabir Mohammad, Nazullah Khan, Mushtaq Ahmed, Sadia Sethi (Pakistan Journal of Ophthalmology, 2010)
Purpose: To study demographics of trachoma patients and their response to azithromycin. Material and Methods: This was observation and clinical assessment study done for one year from June 2006 – June 2007. The study was carried out, in an out patient eye clinic at District Bannu on eye patients, on random basis. The strategy investigated was the use of single dose azithromycin treatment for those who were found to be having clinically active trachoma, as well as all members of their household. All patients were followed for three months and followup was done at one week, one month and three months. Results: 5000 patients were examined randomly during the year 2006-07 for various ocular ophthalmic problems, out of which 120 (2.4%) cases were having signs of acute trachoma. Among these patients, 108 (90%) were female and 12 (10%) were male. With single dose treatment of azithromycin 96 (80%) patients completed their three months follow-up 103 (85.83%) completed one month follow-up and 117 (97.50%) completed 1st week follow-up. Compliance of the patients was 100%. Only two patients got recurrence after 2nd follow-up. Conclusion: There is a very high frequency of trachoma patients in district Bannu and the main victims of the disease were women folk of the community. It is concluded that a single dose of azithromycin is very effective for the treatment of trachoma.